Регулярні ортоскаляриі зображення розширеного графа Динкіна Ẽ₈ та *-алгебри, асоційованої з ним - Кругляк, С.А.; Лівінський, І.В. (Український математичний журнал, 2010)
Получена классификация регулярных ортоскалярных представлений расширенного графа Дынкина Ẽ₈ со специальным характером. С ее помощью описаны тройки самосопряженных операторов А, В, С, спектры которых содержатся в множествах {0,1,2,3,4,5},{0,2,4} и {0,3} соответственно и для которых A+B+C=6I We obtain a classification of regular orthoscalar representations of the extended Dynkin graph Ẽ₈ with special character. Using this classification, we describe triples of self-adjoint operators A, B, and C such that their spectra are contained in the sets {0, 1, 2, 3, 4, 5}, {0, 2, 4}, and {0, 3}, respectively, and the equality A + B + C = 6I is true.